2020
DOI: 10.3390/nu12113330
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Impact of Milk Beverages in Reducing Nutrient Inadequacy among Children Aged One to Five Years in the Philippines: A Dietary Modelling Study

Abstract: Around half of Filipino children are not consuming any dairy products on a given day, which has shown to be associated with increased risk of inadequate nutrient intakes. The current study applies dietary modelling to assess the nutritional impact of meeting dairy recommendations in reducing nutrient inadequacy in children aged one to five years in the Philippines. Dietary intake data of Filipino children aged one to five years (n = 3864) were analyzed from the 8th National Nutrition Survey 2013. Children who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The total daily intake of 30 nutrients was calculated using the first 24-hour recall. Energy intakes were assessed and participants with energy intakes above or below 3SD of the mean were considered implausible [ 9 , 18 ]. All recorded foods and beverages were classified into 12 major food groups and appropriate subgroups.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The total daily intake of 30 nutrients was calculated using the first 24-hour recall. Energy intakes were assessed and participants with energy intakes above or below 3SD of the mean were considered implausible [ 9 , 18 ]. All recorded foods and beverages were classified into 12 major food groups and appropriate subgroups.…”
Section: Methodsmentioning
confidence: 99%
“…This alternative to cow’s milk has a modified fatty acid profiles and additional micronutrients, typically vitamin D, iron, calcium and zinc, with the aim to supplement micronutrient intakes that are often lacking in the overall diet. Previous studies have demonstrated consumption of fortified young children milk or pre-school children milk can improve nutrient intakes and reduce prevalence of nutrient inadequacies [ 9 , 16 , 17 ]. In scenario two, among children who consumed milk of any kind (fortified and unfortified) (“milk consumers” n = 167), we substituted the nutritional composition of their habitual milk with the composition of PCM, volume to volume.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations